Evaluation of different fungicides applied as seed tuber treatments for the control of potato silver scurf - Hervieux, V.; Chabot, R.; Arul, J.; Tweddell, R.J. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 2001)
Silver scurf of potatoes (Solanum tuberosum), caused by the fungus Helminthosporium solani, is an important surface-blemishing disease of potato tubers. The objective of the study was to evaluate the efficacy of different fungicides applied to potato seed tubers for control of silver scurf. Field trials were conducted in Québec province in 1998 and 1999. Potato seed tubers infected with H. solani were treated with either talc, fludioxonil, mancozeb, iprodione, thiabendazole, imazalil or azoxystrobin, and planted at three locations in 1998 and two locations in 1999. The results showed that, under our experimental conditions, the fungicides tested, applied as seed treatments, did not significantly influence total and marketable yields as well as silver scurf severity on daughter tubers at harvest and after different storage periods. In addition, this study showed the influence of the experimental locations on silver scurf development and suggests that soil inoculum plays a role in the epidemiology of the disease.